2012
DOI: 10.1590/s1415-52732012000300007
|View full text |Cite
|
Sign up to set email alerts
|

Food service compliance with ISO 14001 and ISO 22000

Abstract: ObjectiveThe objective of this study was to assess food service environmental and food safety management systems according to two checklists based on ABNT ISO 22000 and 14001. MethodsThis exploratory and descriptive study investigated a-la-carte food services of the Federal District, Brazil. Two checklists were developed to investigate ISO 14001 and 22000 compliance. A total of 37 food services were selected from the list of the Brazilian Association of Bars and Restaurants by simple random sampling. Checklist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…According to a study by Santos et al (2012), who evaluated the performance of two existing laws for implementing quality programs in restaurants in the city of Brasília, it was found that only one of the laws is being enforced because it is more frequently required in the municipal surveillance audits. According to Soto et al (2009), improving these requirements, which are more accurately evaluated by the Health Surveillance, will be effective and sustainable as long as the periodic inspections scheduled by the Health Surveillance are maintained.…”
Section: Resultsmentioning
confidence: 99%
“…According to a study by Santos et al (2012), who evaluated the performance of two existing laws for implementing quality programs in restaurants in the city of Brasília, it was found that only one of the laws is being enforced because it is more frequently required in the municipal surveillance audits. According to Soto et al (2009), improving these requirements, which are more accurately evaluated by the Health Surveillance, will be effective and sustainable as long as the periodic inspections scheduled by the Health Surveillance are maintained.…”
Section: Resultsmentioning
confidence: 99%
“…Other instruments have been validated regarding GMP (Akutsu, Botelho, Camargo, Oliveira, & Araújo, 2005;Araújo et al, 2015;Santos, Akutsu, Botelho, & Zandonadi, 2012), instruments to determine the readiness for change stage (Cattai, Hintze, & Junior, 2010a;Sutton et al, 2003), and to evaluate the understanding, knowledge, attitudes and practice obtaining an overall confidence interval of 95% (Cunha, Stedefeldt, & Rosso, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…With to the goal of ensuring the safety of the food produced, a nutritionist oversees the origin of the raw material as well as plans purchases and coordinates the receipt of the raw materials (Conselho Federal de Nutricionistas, 2006). The role of the nutritionist is related to the implementation of Good Practices and safe food production (Akutsu et al, 2005;Santos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This study included the evaluation of cleaning, the integrity of the primary packaging, and the particularities of each food (Associação Brasileira de Normas Técnicas, 2008; Agência Nacional de Vigilância Sanitária, 2004), however, only a few restaurants adopted a meat packaging recycling program. Santos et al( 2012) observed that lack of concern for environmental issues and non-compliance with the legislation regarding waste collection were evident. Only 29.7% of the facilities evaluated had implemented a system for the separation of recyclable materials.…”
Section: Discussionmentioning
confidence: 99%